Factors associated with antibiotic prescription among healthcare workers at tertiary hospitals in Nairobi County, Kenya - OW Mbuthia; EN Ndonga; SO Odiwour; MW Muraguri (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Globally, there has been an overall decline in the effectiveness of antibiotics resulting in an upsurge in bacterial resistance, increased cost of healthcare and consequent high morbidity and mortality rates. Objective: To determine antibiotic prescription practices among healthcare workers at the Kenyatta National Hospital, Mbagathi, Pumwani Maternity and Mama Lucy Kibaki Hospitals, Nairobi, Kenya. Methods: The study design was a mixture of quantitative and qualitative methods. Self-administered questionnaires were used to gather information from 230 prescribing healthcare workers. Interviews and Focus Group Discussions (FGDs) were conducted purposively with the prescribing healthcare workers and patients to obtain qualitative data. Results: There was a significant difference in the distribution of study participants with regards to the availability of antibiotics prescribing policy (p = 0.05). Only 53 (23%) prescribers prescribed antibiotics as per the policy guide while 51 (22.2%) did not and 126 (54.8%) were not sure. Oral antibiotics (OR = 0.5, 95%CI 0.3-0.9), always referring to the 2016 Kenya Essential Medicines List (KEML) to prescribe antibiotics (OR = 4.2, 95%CI 1.3-13.1), separating antibiograms for inpatient and outpatient departments (OR = 4.3, 95%CI 1.11-15.5), and confidence of healthcare workers to prescribe antibiotics without laboratory tests (OR = 0.3, 95%CI 0.2-0.8) were associated with the prescription of antibiotics. Conclusion: There is need to improve antibiotic prescription practices among healthcare workers in public tertiary hospitals in Nairobi County to promote rational antibiotic use and control bacterial resistance.